Lampu Rambu Lalu Lintas Portable Surya Berbasis IoT: - Vadila, Vadila; Mayati, Iis; Ocsirendi, Ocsirendi; Sulistyo, Eko (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
Traffic congestion is a common issue on disorganized roads. This research designs a traffic sign control system based on the Internet of Things (IoT), utilizing solar energy as the main power source and featuring a portable design for easy relocation according to road requirements. The system employs NodeMCU and Arduino UNO R3 as microcontrollers and uses a battery to store energy from the solar cell. Based on calculations, a 5Ah 12-Volt battery with a power output of 30 Watts requires 9 hours to discharge, while recharging the battery with a 13.2-Volt current takes 8 hours.